Investigates ICT Adoption Among Senior Citizen in Local Community - Rafilan, Nursyahirah; A.Gani, Norhaninah (Jurnal Evolusi, 2021)
The study's main goal is to find out why older adults in Malaysian communities aren't utilising ICT as much as they should, which is a very important problem. The high cost of ICT devices and limited access to technology infrastructure make things very hard for senior citizens. This makes it harder to adapt on technology and highlights the urgent need for low-cost ways to more involved with ICT. Therefore, this study needs to highlight behavioural intention. In order to measure the impact full of behavioural intention, its need to factors technology anxiety and social influence. It shows a significant relationship between behavioural intention and technology anxiety and social influence. A survey conducted online with a quantitative method for the community. Survey questions were given to 160 residents but 110 data were collected from elderly local respondents in Klang Valley focusing on Puncak Alam. This study uses theory Technology Acceptance Model (TAM). Some suggestions include switching from quantitative to qualitative data collection, making events and programmes to get older people to use, and teaching seniors about online safety and security to keep them safe from scams and threats.